Determining unstable game states to aid the identification of perturbations in football - Kim, J.; James, N.; Parmar, N.; Ali, B.; Vuckovic, G. (International Journal of Performance Analysis in Sport, 2019)
Alternative approaches to the reductionist method for analysing football are needed to better understand factors typically not considered, for example off the ball runs by teammates. The dynamical systems approach, where the complex relationships between players is emphasised, predicts that goal scoring opportunities are preceded by instability in the balance between the two teams` behaviours. The aim was to create operational definitions for determining unstable game states to facilitate the identification of perturbations, that is the causes of instability. Validity tests involving four English Premier League (EPL) football coaches and two performance analysts and subsequent reliability tests established five unstable game states; penalty box possession, counter attack, ratio of attacking to defending players, successful cross and successful shot. Eighteen EPL matches were analysed to present exemplar statistics for three teams of different standard (based on final league position) suggesting that teams create unstable situations differently, likely due to individual player characteristics, with home advantage and opposition strength effects, suggesting this may be a component of what constitutes a performance indicator for a team. Future studies need to consider individual player actions that create instability as well as provide objective measures that substantiate findings.